On the margin of the Latin American Boom. City, perspective and postmodernity in "A piel de serpiente" (serpent's skin) by Luis Loayza - Rodríguez Flores, Antonio (2012)
This article is intended to show the value of the novel Una piel de serpiente (A Snake Skin) in the narrative work of writer Luis Loayza. We believe this is an important text because it is a stylistic breakup with his contemporaries. His writing –linked to the French paradigm from the existentialist philosophical tendency to the aesthetics of the nouveau roman– produces a kind of subjectivity as a result of his perception of the world. This aspect, under the context of the Latin American Literary Boom is incompatible and keeps it apart from general interest.